2021
DOI: 10.1152/ajpendo.00565.2020
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte- and late osteoblast-derived NOTUM reduces cortical bone mass in mice

Abstract: Osteoporosis is a common skeletal disease, with increased risk of fractures. Currently available osteoporosis treatments reduce the risk of vertebral fractures, mainly dependent on trabecular bone, whereas the effect on non-vertebral fractures, mainly dependent on cortical bone, is less pronounced. WNT signaling is a crucial regulator of bone homeostasis, and the activity of WNTs is inhibited by NOTUM, a secreted WNT lipase. We previously demonstrated that conditional inactivation of NOTUM in all osteoblast li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
3
4
0
Order By: Relevance
“…55 We detected strong expression of Notum in cultured osteoblasts, which is not surprising given high expression levels described in osteocytes and mature osteoblasts in vivo. 55 Notum deletion in murine osteocytes/late osteoblasts resulted in increased cortical bone mass, which was expected given its role as a Wnt inhibitor. 55 Evidence suggests that the actions of Notum are specific to modulation of Wnt signaling and thus effects on lipid metabolism are unlikely.…”
Section: Induction Of Er Stress With Tunicamycin Was Shown To Inducesupporting
confidence: 62%
See 1 more Smart Citation
“…55 We detected strong expression of Notum in cultured osteoblasts, which is not surprising given high expression levels described in osteocytes and mature osteoblasts in vivo. 55 Notum deletion in murine osteocytes/late osteoblasts resulted in increased cortical bone mass, which was expected given its role as a Wnt inhibitor. 55 Evidence suggests that the actions of Notum are specific to modulation of Wnt signaling and thus effects on lipid metabolism are unlikely.…”
Section: Induction Of Er Stress With Tunicamycin Was Shown To Inducesupporting
confidence: 62%
“…55 Notum deletion in murine osteocytes/late osteoblasts resulted in increased cortical bone mass, which was expected given its role as a Wnt inhibitor. 55 Evidence suggests that the actions of Notum are specific to modulation of Wnt signaling and thus effects on lipid metabolism are unlikely. Further studies are needed to elucidate the role of Lipase A and hepatic lipase in bone, and to determine whether osteoblast lipases are acting cell autonomously, or contributing to lipid metabolism globally.…”
Section: Induction Of Er Stress With Tunicamycin Was Shown To Inducementioning
confidence: 79%
“…Trabecular and cortical bone may respond differently to treatments, and certain WNT signaling pathways have the capacity to regulate the trabecular and the cortical bone compartments separately ( 11 13 ). Previous studies have demonstrated that osteoblast-derived WNT16 and the secreted WNT inhibiting lipase NOTUM are major regulators specifically of cortical bone mass ( 11 , 32 , 33 , 36 ). In contrast, WNT10b and the extracellular WNT signaling modulator RSPO3 mainly regulate trabecular bone mass ( 12 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Karin H Nilsson et al. demonstrated that late osteoblast‐derived NOTUM reduces cortical bone mass (Nilsson et al., 2021). Therefore, NOTUM is crucial for Foxf1 osteogenic differentiation of BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that NOTUM reduced cell growth and cell transfer, and inhibited osteogenic differentiation of BMSCs. Karin H Nilsson et al demonstrated that late osteoblast-derived NOTUM reduces cortical bone mass (Nilsson et al, 2021). Therefore, NOTUM is crucial for Foxf1 osteogenic differentiation of BMSCs.…”
Section: Discussionmentioning
confidence: 99%